Entrepreneurial competences and educational implications in European contexts: a comparative study from a professional perspective - Fariña Sánchez, María Isabel; Suárez Ortega, Magdalena (Revista Española de Educación Comparada, 2023)
Despite the importance of entrepreneurship as a tool for generating employment, economic and social growth in a country, especially in post-pandemic times, and the education and support programmes developed to encourage it, the percentage of entrepreneurial projects that fail continues to increase. The causes include financial, structural, and personal aspects. This research aims, through the perceptions of professional entrepreneurship trainers and advisors, to (1) characterise the situation of entrepreneurship in four European countries with an entrepreneurial impact - Estonia, Ireland, the Netherlands and the United Kingdom -, (2) identify the competences and needs that are necessary for the development of these projects, and (3) highlight the good practices carried out in the Entrepreneurship Education and support programmes from a comparative perspective. The aim is to establish proposals for improvement for the development of entrepreneurial education and support programmes that favour the success of entrepreneurial projects. The methodology is qualitative, applying semi-structured interviews with 15 entrepreneurship advisors with different profiles in entrepreneurship training and belonging to different entities. The content was analysed using NVivo 12 Plus software, carrying out the corresponding procedures for the content analysis of the interviews. The results show, in all countries, the large volume of entrepreneurial projects that are developed, their distribution by gender, area and sectors, and the importance of developing specific and transversal entrepreneurial competences. Furthermore, it also shows how, according to professionals in all contexts, individualised advice, mentoring, training, and social networks favour the development of these competencies and meet the entrepreneurial needs of the users. This shared knowledge confirms the need to continue working on improving training programmes in entrepreneurial competences for the development and success of entrepreneurship.